Exploring dual diagnosis in opioid agonist treatment patients: a registry-linkage study in Czechia and Norway - Rolová, Gabriela; Skurtveit, Svetlana; Gabrhelík, Roman; Mravčík, Viktor; Odsbu, Ingvild (Addiction science & clinical practice, 2024)
BACKGROUND: Knowledge of co-occurring mental disorders (termed 'dual diagnosis') among patients receiving opioid agonist treatment (OAT) is scarce. This study aimed (1) to estimate the prevalence and structure of dual diagnoses in two national cohorts of OAT patients and (2) to compare mental disorders between OAT patients and the general populations stratified on sex and standardized by age. METHODS: A registry-linkage study of OAT patients from Czechia (N = 4,280) and Norway (N = 11,389) during 2010-2019 was conducted. Data on mental disorders (F00-F99; ICD-10) recorded in nationwide health registers were linked to the individuals registered in OAT. Dual diagnoses were defined as any mental disorder excluding substance use disorders (SUDs, F10-F19; ICD-10). Sex-specific age-standardized morbidity ratios (SMR) were calculated for 2019 to compare OAT patients and the general populations. RESULTS: The prevalence of dual diagnosis was 57.3% for Czechia and 78.3% for Norway. In Czechia, anxiety (31.1%) and personality disorders (25.7%) were the most prevalent, whereas anxiety (33.8%) and depression (20.8%) were the most prevalent in Norway. Large country-specific variations were observed, e.g., in ADHD (0.5% in Czechia, 15.8% in Norway), implying differences in screening and diagnostic practices. The SMR estimates for any mental disorders were 3.1 (females) and 5.1 (males) in Czechia and 5.6 (females) and 8.2 (males) in Norway. OAT females had a significantly higher prevalence of co-occurring mental disorders, whereas SMRs were higher in OAT males. In addition to opioid use disorder (OUD), other substance use disorders (SUDs) were frequently recorded in both countries. CONCLUSIONS: Results indicate an excess of mental health problems in OAT patients compared to the general population of the same sex and age in both countries, requiring appropriate clinical attention. Country-specific differences may stem from variations in diagnostics and care, reporting to registers, OAT provision, or substance use patterns.
Keywords: Young Adult; diagnóza dvojí (psychiatrie); Diagnosis, Dual (Psychiatry); Male; opiátová substituční terapie; mladý dospělý; poruchy spojené s užíváním opiátů; úzkostné poruchy; Opioid-Related Disorders; Mental Disorders; Adolescent; sexuální faktory; Česká republika; Opioid use disorder; Norway; Analgesics, Opioid; Adult; prevalence; Registry-based study; Psychiatric comorbidity; Aged; dospělí; mužské pohlaví; senioři; poruchy osobnosti; registrace; opioidní analgetika; duševní poruchy; Personality Disorders; mladiství; Czech Republic; lidé; ženské pohlaví; Anxiety Disorders; Humans; Sex Factors; Prevalence; Opioid agonist treatment; Norsko; Registries; Dual diagnosis; Female; lidé středního věku; Opiate Substitution Treatment; Middle Aged